NMR Relaxivities of Paramagnetic, Ultra‐High Spin Heterometallic Clusters within Polyoxometalate Matrix as a Function of Solvent and Metal Ion. Issue 19 (27th July 2022) - Schork, Nicolas; Ibrahim, Masooma; Baksi, Ananya; Krämer, Steffen; Powell, Annie K.; Guthausen, Gisela
Abstract: Selectivity and image contrast are always challenging in magnetic resonance imaging (MRI), which are – inter alia – addressed by contrast agents. These compounds still need to be improved, and their relaxation properties, i. e., their paramagnetic relaxation enhancement (PRE), needs to be understood. The main goal is to improve specificity and relaxivities, especially at the high magnetic fields currently exploited not only in material science but also in the medical environment. Longitudinal and transverse relaxivities, r 1 and r 2, which correspond to the longitudinal and transverse relaxation rates R 1 and R 2, normalized to the concentration of the paramagnetic moieties, need to be considered because both contribute to the image contrast. 1 H‐relaxivities r 1 and r 2 of high‐spin heterometallic clusters were studied containing lanthanide and transition‐metal ions within a polyoxometalate matrix. A wide range of magnetic fields from 0.5 T/20 MHz to 33 T/1.4 GHz was applied. The questions addressed here concern the rotational and diffusion correlation times which determine the relaxivities and are affected by the solvent's viscosity. Moreover, the variation of the lanthanide and transition‐metal ions of the clusters provided insights into the sensitivity of PRE with respect to the electron spin properties of the paramagnetic centers as well as cooperative effects between lanthanides and transition metal ions. Abstract : Paramagnetic relaxation enhancement of polyoxometalate‐based ultra‐high‐spin clusters Ln30 M8 depends not only on the electronic correlation times of the lanthanide and metal ions but also on the diffusion and rotational correlation times: The dispersion of r 1 and r 2 over Larmor frequencies from 20 MHz to 1.4 GHz reflects the complex interplay of the diverse contributing factors.